2009
DOI: 10.1074/jbc.m109.014191
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Investigation of the Roles of FdmM and FdmM1 in Fredericamycin Biosynthesis Unveiling a New Family of Oxygenases

Abstract: Fredericamycin (FDM) A, a highly oxidized aromatic pentadecaketide natural product, exhibits potent cytotoxicity and has been studied as a new anticancer drug lead. The FDM biosynthetic gene cluster has been previously cloned from Streptomyces griseus ATCC 49344 and successfully expressed in the heterologous host Streptomyces albus J1074. The fdmM and fdmM1 genes code for two proteins with high sequence homology to each other but unknown function. In-frame deletion of each of the genes from the fdm cluster was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 23 publications
(46 reference statements)
3
23
0
Order By: Relevance
“…Recently, Shen and co-workers reported that PnxE1 and PnxE2 homologs FdmM and FdmM1 were responsible for the oxygenation at C6 and C8 of the polyketide intermediate by gene inactivation studies. 33 However, this oxygenation activity is the same as that proposed for PnxH and PnxI described above. Therefore, at the moment, we propose that three of PnxH, PnxI, PnxE1 and PnxE2 might be responsible for the oxygenation at C6, C8 and C10.…”
Section: Cloning Of Fd-594 Biosynthetic Gene Cluster F Kudo Et Alsupporting
confidence: 67%
“…Recently, Shen and co-workers reported that PnxE1 and PnxE2 homologs FdmM and FdmM1 were responsible for the oxygenation at C6 and C8 of the polyketide intermediate by gene inactivation studies. 33 However, this oxygenation activity is the same as that proposed for PnxH and PnxI described above. Therefore, at the moment, we propose that three of PnxH, PnxI, PnxE1 and PnxE2 might be responsible for the oxygenation at C6, C8 and C10.…”
Section: Cloning Of Fd-594 Biosynthetic Gene Cluster F Kudo Et Alsupporting
confidence: 67%
“…Both the TtnD decarboxylase and TtnI P-450 oxygenase also shown some degree of substrate promiscuity, as exemplified by the accumulation of TTN D-4 in the ΔttnD mutant strain SB13013 and subsequent conversion of TTN D-4 to TTN in the ΔttnD complementation strain SB13013. 6b Substrate promiscuity is common for enzymes from secondary metabolite biosynthetic machinery, 9 a property that has been extensively exploited for natural product structural diversity by combinatorial biosynthesis methods. In the absence of the TtnD carboxylase activity, TTN D-4 apparently could undergo C-5 reduction to afford TTN D-2 and TTN D-3, shunt metabolites whose formation most likely resulted from adventitious activities in the ΔttnD mutant SB13013 fermentation.…”
mentioning
confidence: 99%
“…These facts support the proposal that the amide nitrogen of FDM A is incorporated following installation of the polycyclic ring system. The isolation of four new FDM analogs, FDM M-1, FDM M-2, FDM M-3, and FDM M1-1, all sharing the same FDM C scaffold, from the ⌬fdmM or ⌬fdmM1 mutant strains further supports the idea of amide formation as a postpolyketide synthase tailoring step (20) (Fig. 2).…”
mentioning
confidence: 67%
“…1) (20). Among these aromatic polyketides, lysolipin X (LlpA) (13) possesses a lactam ring like FDM A. Pradimicin A (PdmN) (28) contains an amide bond formed putatively using D-Ala as the amino donor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation